SUHENTO LIAUW DAN SOTERIOLOGI:TINJAUAN KRITIS DARI PERSPEKTIF ALKITAB - Lawolo, Mey Daman; Tasey, Arianto; Buaya, Nur Hayati (STT-RAI Batam, 2025)
Suhento Liauw has a unique understanding of the doctrine of salvation (soteriology). The uniqueness of his teaching has become widespread through his writings published on social media. In his teaching, Suhento prioritizes soteriology over other doctrinal topics without realizing the correspondence of the doctrines. In addition, Christ’s redemption applies to all people making it possible for all to be saved. In addition, even if someone has responded to the gift of salvation, it is certain that he will lose his salvation. Using the qualitative method of literature, the authors finds Suhento Liauw’s soteriology contradicts the truth of Scripture. By analyzing the biblical revelation, soteriology is one of the doctrinal topics that does not stand alone without other doctrines. In soteriology, God applies the work of Christ to His chosen people and guarantees the salvation of His children through the work of His providence. The grace of salvation not only frees people from sin, but gives the elect the responbility and privilege to share in the work of salvation initiated by God Himself through the preaching of the gospel.